2017
DOI: 10.1002/lno.10724
|View full text |Cite
|
Sign up to set email alerts
|

Benthic N pathways in illuminated and bioturbated sediments studied with network analysis

Abstract: The regulation of benthic nitrogen (N) cycling by multiple interactions among bacteria, macrofauna, and primary producers is poorly understood. We hypothesized that a biodiverse benthic system should better exploit the benthic N‐availability and retain N than a simpler one. Retention occurs by avoiding losses both to the water column via increased recycling and to the atmosphere via decreased N2 fluxes and by limiting energy‐costly processes as N‐fixation. We also hypothesized that primary producer‐bacterial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 79 publications
0
21
0
2
Order By: Relevance
“…The potential for N 2 : Ar to be used in combination with IPT may be of benefit when working in shallow environments where plants, meio‐ and macrofaunal activity creates heterogeneous sediments, and therefore IPT assumptions could be invalid or too complex to be determined with a single method (Magri et al ). In previous studies, N 2 : Ar has been shown to overestimate N 2 production in permeable sediments under advective pore‐water flow (Cook et al ), underestimated N 2 production in sediments reworked by macrofauna (Ferguson and Eyre ) and in estuarine sediments with hypoxic bottom water (Crowe et al ), and give comparable results (Eyre et al ; Deek et al ) relative to whole‐core‐IPT measurements.…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 2 more Smart Citations
“…The potential for N 2 : Ar to be used in combination with IPT may be of benefit when working in shallow environments where plants, meio‐ and macrofaunal activity creates heterogeneous sediments, and therefore IPT assumptions could be invalid or too complex to be determined with a single method (Magri et al ). In previous studies, N 2 : Ar has been shown to overestimate N 2 production in permeable sediments under advective pore‐water flow (Cook et al ), underestimated N 2 production in sediments reworked by macrofauna (Ferguson and Eyre ) and in estuarine sediments with hypoxic bottom water (Crowe et al ), and give comparable results (Eyre et al ; Deek et al ) relative to whole‐core‐IPT measurements.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…However, to date anammox has not been shown to be a significant process in sediments in which the impacts of bioturbation have been investigated (Bonaglia et al , ) and very few studies have been carried out on how bioturbation may impact benthic N‐fixation (Bertics et al ). As such the presence of benthic animals and their burrowing activities may produce as yet unknown antagonistic or synergistic effects on benthic N cycling processes (Magri et al ).…”
Section: Environmental Challenges When Applying the Iptmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, species that seem redundant under natural conditions may be important for ecosystem functioning when ecosystems are disturbed [10]. The understanding of the biogeochemical dynamics in environments characterized by high biodiversity is strongly limited by the complex and multiple interactions among species [11]. In strongly anthropized environments, generally associated with a strong loss of biodiversity, identification of important ecological niches is even more difficult.…”
Section: Introductionmentioning
confidence: 99%
“…free sulfides and metal ions) around and within the roots, where they otherwise may induce physiological stress and damage to the plant (Geurts et al, 2009;Koch & Mendelssohn, 1989). In addition, ROL may promote aerobic microbial processes that mobilise nutrients and trace-elements from recalcitrant organic matter (Harvey, Tuttle, & Bell, 1995;Magri et al, 2018) or, on the contrary, favour nutrient immobilisation (e.g. phosphorous and iron) via adsorption or precipitation (e.g.…”
mentioning
confidence: 99%